PENGARUH MARKET DAY (BAZAR) TERHADAP MEMBANGUN JIWA WIRAUSAHA MAHASISWA UNSIQ JAWA TENGAH DI WONOSOBO - Eni Candra Nurhayati (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
A country that has many entrepreneurs (entrepreneurs) is a country whose economy has a fast potential to advance and can be classified as a prosperous country. Therefore, if entrepreneurial learning is not on the national agenda of a country, the ideal to escape poverty and rise to prosperity is only utopia. Indonesia has around 400,000 entrepreneurs, or around 0.18 percent of the population. So that Indonesia still needs 12 more entrepreneurs than it is today. School or education is a very strategic place to grow the entrepreneurial spirit. Overall and based on the research carried out the researcher can draw the conclusion that market day activities (bazaars) significantly influence the building of the spirit of student entrepreneurship. It can be proven that the provision of market day (bazaar) (X) activities can influence the development of student entrepreneurial spirit at 58%. While the remaining 42% is caused by other independent variables not examined. The existence of this influence can be proven by t count = 17,342> t table 0,1256 so that Ho is rejected and thus Ha is accepted. Ho's rejection was reinforced by the forecasting error value of 0,000 which showed that the significance used was 0.05 or 5% so that it can be seen that the hypothesis is suspected of providing market day activities (bazaars) influencing the development of the student entrepreneurial spirit. Based on the results of research and data processing using SPSS, it can be seen that the provision of market day activities (bazaars) on Campus is able to build the spirit of Student Entrepreneurs. This confirms that the market day activities (bazaars) in UNSIQ Central Java in Wonosobo have a positive influence on the spirit of Student Entrepreneurs and the Entrepreneurship Course it self.